2016
DOI: 10.1016/j.energy.2015.12.051
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to determine air leakage in heat pump clothes dryers

Abstract: Although heat pump clothes dryers offer the potential to save a significant amount of energy as compared to conventional vented electric dryers; they are prone to air leakage that can limit their efficiency gain. This study serves to develop a novel method of quantifying leakage, and to determine specific leakage locations in the dryer drum and air circulation system. The method follows an American Society of Testing and Materials (ASTM) standard, which is used to determine air leakage area in a household vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It can be found that the leakage increases sharply with the increase of leak aperture. Its variation trend confirms the analysis discussed in Equation (7). Therefore, in the process of air-leakage detection with an ultrasonic detector, the system pressure can be set to a certain stable value due to its slight influence on the leakage rate, and the size of the leak aperture can be computed directly by the leakage rate measured by the flow-meter.…”
Section: Effects Of System Pressure and Leak Aperture On The Leakage Ratesupporting
confidence: 73%
See 1 more Smart Citation
“…It can be found that the leakage increases sharply with the increase of leak aperture. Its variation trend confirms the analysis discussed in Equation (7). Therefore, in the process of air-leakage detection with an ultrasonic detector, the system pressure can be set to a certain stable value due to its slight influence on the leakage rate, and the size of the leak aperture can be computed directly by the leakage rate measured by the flow-meter.…”
Section: Effects Of System Pressure and Leak Aperture On The Leakage Ratesupporting
confidence: 73%
“…The technology of ultrasonic and infrared detections that have appeared in recent years was also explained in detail. In addition, Bansal et al [7] developed a novel method to regulate the air-leakage area in a household ventilation system by fan pressurization. With this technique, the leakage area can be revealed by an assessment of the leakage volumetric flow-pressure relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a drying system is characterized by various indices, including energy efficiency, thermal efficiency, volumetric evaporation rate, specific heat consumption, surface heat losses, unit steam consumption, and others which have been defined to reflect the requirements of various drying technologies [30]. Energy efficiency is critical because energy consumption strongly affects the drying costs [31].…”
Section: Drying Efficiencymentioning
confidence: 99%
“…However drying characteristics and SMER were not discussed. Recently, Bansal et al [11] reported a study on the method to determine air leakage in heat pump clothes dryer. In the system, heat pump was employed to produce hot drying air to tumbler dryer instead of using conventional electric heater.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested and tested a procedure to determine air leakage in heat pump clothes dryers. Mainly the studies related to clothes dryer found in literature dealt with tumble dryer [11][12][13][14][15] and only very limited studies related to cabinet heat pump clothes dryer.…”
Section: Introductionmentioning
confidence: 99%